Fitness Influence on the Transformation of Body Composition and on the Improvement of Aerobic Sustainability in Women - Myrtaj, Nazim; Elezi, Abdulla; Gontarev, Seryozha; Bilalli, Eglantina ("St. Cyril and St. Methodius" University of Veliko Tarnovo, 2022)
The purpose of this research is to determine the effects of a specialised two-month fitness programme with strength exercises on the body composition and aerobic endurance in recreational women. The research included a group of women aged 18–35 who had not previously been engaged in recreational exercises in fitness centres. The sample included 50 women who exercised at the Fivestar fitness centre in Gjilan, and who underwent the abovementioned programme. The composition of the body was evaluated using a Tanita BC-601 device and the bioelectrical impedance analysis (BIA), which was conducted as a reference method in the research related to the analysis of body composition. For this research, the following variables of body composition and aerobic endurance were applied: body height (BH), body weight (BW), body mass index (BMI), body fat percentage (BFP), muscle mass (TBM), bone mass or density (BMD), calorie expenditure (DCI), body vitality (BMR), body water intake (TBW), visceral fat intake (AVF), and the Rockport fitness test for aerobic endurance (ROFT). For the dependent group, the T-test analysis was applied through statistical methods. The results obtained after statistical processing showed that, in relation to the two-month programme three times a week (24 trainings), physical exercises in the fitness can affect the reduction of subcutaneous adipose tissue, and thus reduce the risk of various cardiovascular diseases. In addition to reducing fat mass with strength exercises in the fitness, there was also an improvement in aerobic endurance. This shows that, besides aerobic exercise, weight training should be applied to increase aerobic capacity.